What determines customers' continuance intention of FinTech? Evidence from YuEbao. Issue 8 (11th September 2019) - Wang, Zhenning; GUAN, Zhengzhi (Gordon); Hou, Fangfang; Li, Boying; Zhou, Wangyue
Abstract : Purpose: The purpose of this paper is to investigate the effects of trust in service and structural assurance on the continuance intention of FinTech services, and the roles of technical factors (i.e. situational normality and system quality) and social factors (i.e. herding and subjective norm) in developing trust in service and structural assurance. YuEbao is selected as the subject as it is a representative example of FinTech services in China. Design/methodology/approach: A survey questionnaire was deployed and a ten-point sliding scale with two-decimal points was applied to improve the accuracy of the questionnaire. Partial least squares structural equation modeling was used to analyze the data. Findings: Trust in service and structural assurance can encourage continuance intention of FinTech service. System quality, situational normality and subjective norm can boost the development of trust in service. Both herding and subjective norm can affect structural assurance significantly. Research limitations/implications: The study highlights the important roles played by technical factors (i.e. situational normality and system quality) and social factors (i.e. herding and subjective norm) in developing the two levels of trust (i.e. trust in service and structural assurance). It also validates the influences of trust in service and structural assurance on encouraging customers' continuance intention in the novel context of FinTech. Practical implications: The findings of this study can be used by practitioners to encourage customers to continue using their FinTech services. To encourage continuance, service providers can improve the quality of their system, design the system to be aligned with customers' using habits and show customers that their close friends are also using the service. Originality/value: This study adds to the existing body of trust literature by investigating the direct effects of trust in service and structure assurance on continuance intention and how these two levels of trust are developed from technical and social aspects. It generates interesting insights into customers' continuance behavior of FinTech services.